Evaluation of productivity of sexually precocious Nelore heifers - Terakado, Ana Paula Nascimento [UNESP]; Pereira, Marcio Cinachi; Yokoo, Marcos Jun; Albuquerque, Lucia Galvão de [UNESP] (Cambridge Univ Press, 2015)
The objectives of the present study were to investigate the influence of yearling weight on the occurrence of early pregnancy and to determine differences between precocious and non-precocious heifers in terms of pre- and postnatal calf mortality, calf weight and height, mature cow weight, and stayability of the cow in the herd. Data from 26 977 females of a Nelore herd that participated in the breeding season between 1986 and 2004 were analyzed. The influence of yearling weight on sexual precocity and differences between precocious and non-precocious heifers in pre- and postnatal calf mortality and stayability were analyzed using the GENMOD procedure of the SAS program. Differences in the growth traits between precocious and non-precocious animals were estimated by contrast analysis. Three groups were analyzed for postnatal mortality: first calving of the heifers, calves born from the third calving and all offspring of the cow. In order to have a standardized calving to conception period for all females (precocious and non-precocious), calves born from the second calving were not included in the analysis. This was necessary because the first calving to conception period (days open) of precocious heifers was longer than for non-precocious due to farm reproductive management. No differences in postnatal mortality rates, from the third calving, were observed between the two groups of heifers studied. Analysis of all offspring of the dams showed a 9% higher probability of death of calves born to precocious heifers compared with calves born to non-precocious heifers. With respect to stayability, precocious heifers presented 33% greater odds to remain in the herd until 5 and 6 years of age and 28% greater odds to remain in the herd until 7 years when compared with non-precocious heifers. Precocious heifers weaned calves (205 days) significantly heavier than non-precocious ones, 1.410 and 0.797 kg considering the weaning weights of all offspring and of the third calving, respectively. With respect to sexual precocity, the results suggest that the probability of heifers to become pregnant at 16 months of age increases with increasing weight. However, heifers weighing more than 240 kg present practically the same pregnancy probability. Nevertheless, exposure of heifers during the early breeding season is recommended for beef cattle herds raised in tropical regions in view of the numerous benefits demonstrated here.
Keywords: Early pregnancy; Mortality rate; Stayability; Weaning weight; Yearling weight